Song among the ruins - Schull, Willaim J. (Harvard University Press, 1990)
This book recounts the personal odyssey of this Westerner in the Orient. Through Schull's keen eyes we observe the nation's gravitation toward things American during the Occupation years, when General MacArthur's influence on the Japanese seemed unbounded. Yet Schull also witnessed a rekindling of national spirit in the 1950s that has allowed Japan to surpass, in peacetime, the econimic accomplishments of the nation it could not defeat in war.